Sex-specific associations of evening blood pressure burden and cardiac load with nocturia severity in the Japanese at high-risk of cardiovascular disease. (14th October 2021) - Nagai, M; Hoshide, S; Kario, K
Abstract: Background: Earlier epidemiologic studies have reported a significant relationship between hypertension and nocturia. However, the underlying pathophysiology has not been established. We hypothesized that blood pressure (BP) burden, the classes of antihypertensive agents and cardiac load were associated with severity of nocturia, and that these associations might be moderated by gender. Purpose: To investigate the relationships of home BP (HBP) level, the class of antihypertensive agent, brain natriuretic peptide (BNP) with nocturia severity, and to investigate these associations stratified by gender in the Japanese at high-risk of cardiovascular disease. Methods: In the Japan Morning Surge-Home Blood Pressure Study, measurements of HBP at evening (mean 11.2 days) as well as BNP were performed in the 4310 patients with one or more cardiovascular risks (64.9 years old, male 47%). A self-administered questionnaire included items on nocturia was used. Results: According to the number of nocturia (no void: n=2382; one void: n=847; >2 voids per night: n=1082), significant associations of systolic BP (SBP) at evening (130 vs 130 vs 132 mmHg, p<0.0001) and logBNP (1.20 vs 1.30 vs 1.42, p<0.0001) were observed with nocturia severity. In the multinomial logistic regression analysis adjustment for confounders including age, smoking, total cholesterol, fasting blood glucose, HbA1c and clinic SBP, the use of diuretics (OR: 1.26, 95% CI: 1.06–1.52, p<0.05) was significantly associated with one nocturnal void, while evening SBP (OR: 1.009, 95% CI: 1.003–1.014, p<0.01) and logBNP (1.43, 95% CI: 1.19–1.73, p<0.001) were significantly associated with multiple nocturnal voids. While no significant interaction was found between evening SBP and logBNP for multiple nocturnal voids in the total population, a significant interaction was found between evening SBP and logBNP for multiple nocturnal voids in females (p<0.05). Conclusions: In this study, the use of diuretics was a significant indicator of single nocturnal void, while evening SBP and BNP were those of multiple nocturnal voids in the high-risk Japanese population. Specifically, in the females, treatment to reduce BP burden as well as cardiac overload might be important to improve sleep disturbance caused by nocturia. FUNDunding Acknowledgement: Type of funding sources: None.